Guiding World GW - sulistia indah (Program Studi Bimbingan dan Konseling, 2018)
As a professional, teacher should find best strategies in encouraging students’ motivation in learning. Students who are learning English also believe that learning English is learning how to speak. Teaching speaking means employ some strategies, methods and approaches to encourage students’ mood and motivation to speak. In On the other hand, the comprehensibility between participants in the conversation also becomes significant. Based on the observation during the teaching and learning process in the study programs of counceling and guidance at STKIP Bima, it was found that the students’ abilities, motivations, and curiosities in speaking English decreased. They were afraid to practice their speaking ability. Therefore, Asset Based Thinking (ABT) was proposed as in motivating the students to practice and improve their speaking ability. ABT Method is a method that focuses on how lecturer motivated the students to find their strength (potential, skills, knowledge and ability) and how they use the strength as an asset in reaching their target of learning. the participants were 30 students from Counseling and Guidance Study Program of STKIP Bima. The data were Collected by observing the students’ pre activities and post activities, and oral Interview was conducted in getting the information about the students’ speaking ability. The data were analized by using IBM SPSS Ver. 23. Through the analysis it was found that For the reason, the statistic count < statistic table (6.00 < 152). The analysis promoted that the students’ motivation in practicing their speaking ability after taught by using ABT would significantly increase rather than students’ motivation before they were taught by using ABT.